Lithium ion battery and power-using device

By adding characteristic elements to the positive electrode active material layer of lithium-ion batteries and optimizing the porosity of the membrane, the problems of by-product erosion and blockage are solved, the cycle life is extended and the DC internal resistance growth rate is reduced, and the high energy density and large-scale charge and discharge capabilities are achieved.

CN119764531APending Publication Date: 2025-04-04JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510131911.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the high-speed cycle of existing lithium-ion batteries, by-products erode the positive electrode sheet and block the lithium-ion transmission channel, resulting in battery capacity attenuation and increase of DC internal resistance, and insufficient cycle life and safety.

Method used

By adding characteristic elements to the positive electrode active material layer, combining the porosity of the separator, controlling the ratio change rate of fluorine and carbon content, reducing the accumulation of by-products in the battery, and reducing the DC internal resistance growth rate.

Benefits of technology

It realizes that while maintaining high energy density and large-scale charging and discharging capabilities of lithium-ion batteries, it extends the cycle life, reduces the DC internal resistance growth rate, and improves the safety of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764531A_ABST
    Figure CN119764531A_ABST
Patent Text Reader

Abstract

The present application proposes a lithium-ion battery and an electrical device, including a diaphragm and a positive electrode sheet with a porosity p of 30-45%, the positive electrode sheet including a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer including a positive electrode active material, a characteristic element is added to the positive electrode active material, and the number of atoms of the characteristic element accounts for a ratio a of 0.1-0.9% of the total number of atoms of all elements in the positive electrode active material layer, and the lithium-ion battery cycle test and analysis of the ratio T of the fluorine element and the carbon element content in the cross section of the positive electrode active material layer during the cycle process ΔT satisfies: 0<ΔT / (a+p)≤100%. By adding characteristic elements to the positive electrode active material, by constraining the ratio a of the characteristic elements to match the porosity p of the diaphragm, the generation of by-products in the electrochemical system of the battery is reduced, and the ratio of the ratio T of the fluorine element and the carbon element content during the cycle process ΔT to (a+p) can be achieved to be no more than 100%, ensuring a low degree of by-product accumulation and improving the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrical devices, and in particular to a lithium-ion battery and an electrical device. Background Art

[0002] As the demand for high-power output of electrical devices grows, the requirements for the performance of lithium-ion batteries are also getting higher and higher. For example, while maintaining high energy density and high-rate charge and discharge capabilities, they also need to achieve longer cycle life and greater safety in use.

[0003] Existing lithium-ion batteries usually include a shell, an electrolyte and a core, and the core is formed by winding a positive electrode sheet, a separator and a negative electrode sheet. In order to improve the migration efficiency of lithium ions, a separator with a higher porosity is usually used. During high-rate cycling, due to the large overpotential at the end of charge and discharge, the by-products from the electrolyte and the negative electrode will, on the one hand, corrode the positive active material layer of the positive electrode sheet, causing irreversible decay of the battery capacity. On the other hand, the by-products will accumulate in the gaps between the positive active material particles, blocking the lithium ion transmission channel on the positive electrode sheet, reducing the conductivity of the positive electrode sheet, and the DC internal resistance (DCR) of the battery will increase at a high rate, accelerating battery aging.

[0004] At present, the main technical route to deal with the high loss of the battery's electrochemical system caused by the charge and discharge cycle is to coat the surface of the positive electrode active material to form a protective layer to reduce the impact of byproducts during overpotential, thereby extending the normal cycle life of the battery. However, an overly dense and thick protective layer will cause the interface impedance of the positive electrode sheet to increase, and the kinetic performance of the charged particles in the system will be limited, limiting the high-rate input and output of the battery. There are still problems such as low capacity retention and fast performance decay under high-rate cycling conditions. Summary of the invention

[0005] In order to solve the above problems and achieve a longer cycle life while maintaining high energy density and high-rate charge and discharge capabilities, the first aspect of the present application provides a lithium-ion battery, including a shell, a core and an electrolyte, the core is formed by winding a positive electrode sheet, a separator and a negative electrode sheet, the porosity p of the separator is 30-45%, the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer formed on at least one surface of the positive electrode collector, the positive electrode active material layer includes a positive electrode active material, a characteristic element is added to the positive electrode active material, and the ratio a of the number of atoms of the characteristic element to the total number of atoms of all elements in the positive electrode active material layer is 0.1-0.9%, the lithium-ion battery is subjected to a cycle test and the change rate ΔT of the ratio T of the fluorine element and the carbon element content in the cross section of the positive electrode active material layer during the cycle is analyzed, and the change rate ΔT further satisfies: 0<ΔT / (a+p)≤100%. By adding characteristic elements to the positive electrode active material, the characteristic elements can enhance the structural stability of the positive electrode active material layer, the porosity p of the diaphragm affects the degree of side reactions, and the rate of change ΔT of the ratio of the fluorine element to the carbon element content during the cycle can reflect the degree of accumulation of by-products in the electrochemical system. The proportion a of the characteristic elements is constrained to match the porosity p of the diaphragm to reduce the generation of by-products in the electrochemical system of the battery, so that the ratio of the rate of change ΔT of the ratio of the fluorine element to the carbon element content during the cycle to (a+p) is not greater than 100%, which can ensure that the degree of by-product accumulation is low, and the battery can maintain good cycle performance and a low DCR growth rate.

[0006] In some optional embodiments, the porosity p is tested by:

[0007] S11: Prepare a sample of the diaphragm with a size of 200*100 mm, soak it in dimethyl carbonate (DMC) three times, and then dry it in a vacuum oven at 60°C for 2 hours. After the sample is cooled, the surface density ρ is obtained by weight area ratio. 面 ;

[0008] S12: measuring the average thickness d of the diaphragm sample; and

[0009] S13: Calculate the porosity using the formula, P = {1-[ρ 面 / (0.96*d)]}*100%;

[0010] The test method of the atomic number ratio a of the characteristic element is:

[0011] S21: preparing the positive electrode sheet, soaking it in DMC for three times, and then drying it in a vacuum oven at 60° C. for 2 hours, and preparing a cross-section of the positive electrode sheet by argon ion polishing technology after the sample is cooled; and

[0012] S22: using CP-EDS to perform a surface scan on the cross-section corresponding to the positive electrode active material layer on the cross-section slice, measure all elements in the surface scan area, and obtain an atomic number ratio a of characteristic elements;

[0013] The test method for the change rate ΔT of the ratio T of the fluorine element to the carbon element content during the cycle is:

[0014] S31: the lithium-ion battery is charged and discharged 300 times under constant current conditions of 2C charging rate and 10C discharging rate and a working voltage of 2.5-4.2V, and the two groups of positive electrode sheets after the first cycle and the 300th cycle are removed, respectively, soaked in DMC three times, and then dried in a vacuum oven at 60° C. for 2 h;

[0015] S32: After the two groups of positive electrode sheet samples are cooled, cross-section slices of the two groups of positive electrode sheets are prepared by argon ion polishing technology, and the cross-sections corresponding to the positive electrode active material layers on the cross-section slices of the two groups of positive electrode sheets are locally scanned by the CP-EDS method, and the F / C element ratios T1 and T2 in the scanned areas of the two groups of positive electrode sheets are calculated respectively. 300 ;as well as

[0016] S33: Calculate the change rate ΔT(%) using the formula: ΔT(%)=(T 300 -T1) / (T1)*100%.

[0017] In some optional embodiments, the positive electrode active material is a composite lithium metal oxide, specifically: a lithium nickel cobalt manganese oxide with a layered crystal structure, and the chemical formula is: LiNi x Co y Mn z D j O2, wherein 0.8≤x≤0.9, 0.01≤y≤0.1, 0.01≤z≤0.1, j=1-x–yz, D is the characteristic element, and the characteristic element D is any one or more of Al, Sr, Ti, Zr, Nb and W. The characteristic element D can improve the stability of the positive electrode active material layer by lattice doping and substitution, surface modification and coating, improving electronic and ionic conductivity, reducing cation mixing and / or inhibiting lattice oxygen loss.

[0018] In some optional implementations, the lithium-ion battery measures the DC internal resistance DCR according to the following steps:

[0019] S34: At room temperature (25±2°C), the lithium ion battery that has completed one cycle of charge and discharge and the lithium ion battery that has completed 300 cycles of charge and discharge are respectively charged again to their charge cut-off voltage of 4.2V, and then charged at a constant voltage to a current equal to 0.025C, and left to stand for 10 minutes;

[0020] S35: At room temperature (25±2°C), the lithium-ion battery that has been left to stand is first discharged at a rate of 0.25C for 3 seconds to measure a voltage V1, wherein the discharge current corresponds to I1 amperes, and then discharged at a rate of 2.5C for 3 seconds to measure a voltage V2, wherein the discharge current corresponds to I2 amperes; according to the formula: DCR = (V1-V2) / (I2-I1), the DC internal resistance DCR1 value of the lithium-ion battery that has completed one cycle of charge and discharge and the DCR value of the lithium-ion battery that has completed 300 cycles of charge and discharge are obtained respectively. 300 value; and

[0021] S36: Further calculate to obtain the DCR growth rate: ΔDCR = (DCR 300 -DCR1) / (DCR1)*100%, and ΔDCR is 27-80%.

[0022] DCR of a constrained lithium-ion battery after 300 cycles in a 300 cycle test 300 Compared with DCR1 after the first cycle, the DCR growth rate is between 27-80%, which can meet the cycle performance requirements of most existing electrical devices for batteries.

[0023] In some optional embodiments, the positive electrode active material layer is formed by coating a slurry prepared from a positive electrode active material, a positive electrode binder, a positive electrode conductive agent and a solvent on the positive electrode current collector and then drying the slurry, wherein the weight ratio of the positive electrode active material, the positive electrode binder and the positive electrode conductive agent is (95%-98%): (1%-2%): (1%-3%). By optimizing the ratio of the above materials, a balance can be achieved between energy density, conductivity, structural stability and processing performance, thereby achieving the best performance of the lithium-ion battery.

[0024] In some optional embodiments, the negative electrode sheet comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, a negative electrode binder and a negative electrode conductive agent, the negative electrode active material comprises at least two of artificial graphite, natural graphite, silicon-oxygen material and silicon-carbon material, and corresponds to a first negative electrode active material and a second negative electrode active material; wherein the weight ratio of the first negative electrode active material, the second negative electrode active material, the negative electrode binder and the negative electrode conductive agent is (90%-95%): (1%-4%): (1%-2%): (3%-4%). ​​By optimizing the ratio of the above materials, a balance can be achieved between energy density, conductivity, structural stability and processing performance, thereby achieving the best performance of the lithium-ion battery.

[0025] In some optional embodiments, the electrolyte includes lithium hexafluorophosphate, a solvent and a functional agent for improving the performance of the electrochemical system, the solvent includes one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, and the functional agent includes one or more of vinylene carbonate, methyl formate, ethyl acetate, propyl propionate, and fluoroethylene carbonate. The above functional agents work together through different mechanisms to improve the cycle stability, rate performance, low temperature performance and safety of the battery, while inhibiting the growth of lithium dendrites and reducing the decomposition of the electrolyte.

[0026] In some optional embodiments, the lithium-ion battery has a cycle capacity retention rate of 81-93% after 300 cycles of charge and discharge at a 2C charge rate and a 10C discharge rate, which can meet the cycle performance requirements of most existing electrical devices for batteries.

[0027] The second aspect of the present application provides an electric device, comprising a lithium-ion battery according to any one of the above items. Since the lithium-ion battery has the above-mentioned beneficial effects, the electric device provided by the present application supports high-rate charging and discharging, has long-lasting power, and has good use effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0029] Figure 1 is a schematic diagram of the three-dimensional structure of a lithium-ion battery of an optional embodiment of the present application;

[0030] Figure 2 This is a schematic structural diagram of a lithium-ion battery after the roll core part of an optional embodiment of the present application is unfolded;

[0031] Figure 3 It is a cross-sectional schematic diagram of a positive electrode sheet of a lithium-ion battery according to an optional embodiment of the present application.

[0032] Figure 4 It is a capacity retention curve diagram of Example 2 and Comparative Example 1 of the lithium-ion battery of the present application during 300 cycles.

[0033] Reference numerals: 1 - casing, 2 - winding core, 21 - positive electrode sheet, 210 - positive electrode active material layer, 212 - positive electrode current collector, 23 - separator, 25 - negative electrode sheet, 3 - electrolyte. DETAILED DESCRIPTION

[0034] Embodiments of the present embodiment are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present embodiment, and should not be construed as limiting the present embodiment.

[0035] In the description of this embodiment, it should be understood that descriptions involving orientation, such as up, down, front, back, left, right, etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing this embodiment and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on this embodiment.

[0036] In the description of this embodiment, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0037] In the description of this embodiment, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in this embodiment based on the specific content of the technical solution.

[0038] Please refer to Figure 1-Figure 2 , Figure 1 A schematic diagram of the structure of a lithium-ion battery according to an embodiment of the present application is shown. Figure 2 The schematic diagram of the structure after the winding core 2 is partially unfolded is shown.

[0039] The first aspect of the present application provides a lithium ion battery, see Figure 1 , including a shell 1, a winding core 2 and an electrolyte 3, see Figure 2The winding core 2 is formed by winding a positive electrode sheet 21, a separator 23, and a negative electrode sheet 25. The porosity p of the separator 23 is 30-45%. The positive electrode sheet 21 includes a positive electrode collector 212 and a positive electrode active material layer 210 formed on at least one surface of the positive electrode collector 212. Characteristic elements are added to the positive electrode active material. It can be understood that the characteristic elements can be added to the positive electrode active material by lattice doping and substitution, surface modification and coating. Further, the proportion a of the characteristic elements to all elements in the positive electrode active material layer 210 is 0.1-0.9%. The lithium-ion battery is subjected to a cycle test and the change rate ΔT of the ratio T of the fluorine element and the carbon element content in the cross section of the positive electrode active material layer 210 during the cycle is analyzed.

[0040] Specifically, the testing method of the porosity p is:

[0041] S11: Prepare a sample of the diaphragm 23 with a size of 200*100 mm, soak it in dimethyl carbonate (DMC) three times, dry it fully, and then dry it in a vacuum oven at 60°C for 2 hours. After the sample is cooled, the surface density ρ is obtained by weight area ratio. 面 ;

[0042] S12: measuring the average thickness d of the diaphragm 23 sample; and

[0043] S13: Calculate the porosity using the formula, P = {1-[ρ 面 / (0.96*d)]}*100%.

[0044] It can be understood that 0.96 is the raw material density of the diaphragm 23. After the raw material is formed into the diaphragm 23, the porosity becomes larger and the surface density ρ 面 Compared with the raw material under the condition of the same thickness, the surface density is smaller, and the porosity p can be obtained by calculating the ratio of their surface densities.

[0045] Furthermore, the test method for the proportion a of the characteristic elements is:

[0046] S21: Prepare the positive electrode sheet 21, soak it in DMC three times, and then dry it in a vacuum oven at 60°C for 2h. After the positive electrode sheet 21 sample is cooled, use argon ion polishing technology to prepare a cross-section of the positive electrode sheet, wherein the cross section of the slice can be seen in Figure 3 ;as well as

[0047] S22: Use CP-EDS to perform a surface scan on the cross-section corresponding to the positive electrode active material layer 210 on the cross-section slice, measure all elements in the surface scan area, and obtain the atomic number ratio a of the characteristic elements.

[0048] It should be noted that the preparation of the cross-section slice of the positive electrode sheet 21 also includes the following steps:

[0049] S211: Take a lithium-ion battery, let it stand at 25°C for 4 hours, discharge it at a rate of 0.2C to its discharge cut-off voltage of 2.5V, and let it stand for 30 minutes;

[0050] S212: dismantling the lithium-ion battery and obtaining the positive electrode sheet 21, soaking it in DMC for three times, fully drying it, and then baking it in a vacuum oven at 60° C. for 2 hours;

[0051] S213: Cooling the positive electrode sheet 21 and preparing a cross-section of the positive electrode sheet 21 by using an argon ion polishing technique; or

[0052] S214: taking the dried positive electrode sheet 21 after rolling, and directly using argon ion polishing technology to prepare a cross-section of the positive electrode sheet 21 .

[0053] Furthermore, the test method for the change rate ΔT of the ratio T of the fluorine element to the carbon element content during the cycle is:

[0054] S31: the lithium-ion battery is cycled for 300 times at a constant current condition of a 2C charge rate and a 10C discharge rate within a working voltage range of 2.5-4.2V, and the two groups of positive electrode sheets 21 after the first cycle and the 300th cycle are respectively taken out, soaked in DMC three times, fully dried, and then dried in a vacuum oven at 60°C for 2h;

[0055] S32: After the two groups of positive electrode sheets 21 samples are cooled, the cross-sections of the two groups of positive electrode sheets 21 corresponding to the positive electrode active material layer 210 are locally scanned using the CP-EDS method to calculate the F / C element ratios T1 and T2 in the scanned areas of the two groups of positive electrode sheets 21. 300 ;as well as

[0056] S33: Calculate the change rate ΔT(%) using the formula: ΔT(%)=(T 300 -T1) / (T1)*100%.

[0057] Furthermore, the change rate ΔT also satisfies: 0<ΔT / (a+p)≤100%. Among them, the ratio T of the fluorine element and the carbon element content of the positive electrode active material layer 210 is positively correlated with the degree of side reactions in the electrochemical system of the battery. The change rate ΔT of the ratio T can reflect the rate of battery capacity decay, and the greater the porosity p of the diaphragm 23, the more conducive it is to the migration and transmission of lithium ions, which is reflected in enhancing the kinetic performance of the battery system. The greater the proportion a of the characteristic elements, the stronger the ability to resist the corrosion of by-products, but at the same time it will affect the migration and transmission of lithium ions and weaken the kinetic performance of the battery system. The relationship: ΔT / (a+p) can be used as a mathematical model to measure the degree of accumulation of by-products in the electrochemical system. The constraint 0<ΔT / (a+p)≤100% can derive the optimal setting range of the porosity p and the characteristic element content a of the additive, thereby achieving a lithium-ion battery with a longer cycle life while maintaining high energy density and high rate charge and discharge capabilities.

[0058] Furthermore, the application performance of the lithium-ion battery can also be estimated by the DCR growth rate of the battery. Specifically, the DC internal resistance growth rate DCR of the lithium-ion battery is measured according to the following steps:

[0059] S34: At room temperature (25±2°C), the lithium ion battery that has completed one cycle of charge and discharge and the lithium ion battery that has completed 300 cycles of charge and discharge are respectively charged again to their charge cut-off voltage of 4.2V, and then charged at a constant voltage to a current equal to 0.025C, and left to stand for 10 minutes;

[0060] S35: At room temperature (25±2°C), the lithium-ion battery that has been left to stand is first discharged at a rate of 0.25C (corresponding to a current of I1 amperes) for 3 seconds to measure a voltage V1, wherein the discharge current corresponds to I1 amperes, and then discharged at a rate of 2.5C (discharged for 3 seconds to measure a voltage V2, wherein the discharge current corresponds to I2 amperes; according to the formula: DCR = (V1-V2) / (I2-I1), the DC internal resistance DCR1 value of the lithium-ion battery that has completed one cycle of charge and discharge and the DCR value of the lithium-ion battery that has completed 300 cycles of charge and discharge are obtained respectively. 300 value; and

[0061] S36: Further calculate to obtain the DCR growth rate: ΔDCR = (DCR 300-DCR1) / (DCR1)*100%, and ΔDCR is 27-80%. It is understandable that in order to more accurately reflect the change in battery internal resistance during cyclic charge and discharge, the same lithium-ion battery should be used for the above test after completing 1 cycle of charge and discharge and 300 cycles of charge and discharge. DCR is the DC resistance of the battery under the test conditions, which can be used to characterize the sum of the internal resistance of the battery under the action of DC current. The growth rate of DCR can be used to measure the change in the internal resistance of the battery, constraining the DCR of the lithium-ion battery after completing 300 cycles in the 300 cycle test. 300 Compared with DCR1 after the first cycle, the DCR growth rate is between 27-80%, which can meet the cycle performance and discharge power requirements of most existing electrical devices for batteries.

[0062] In some optional embodiments, the positive electrode active material layer 210 is formed by coating a slurry prepared by a positive electrode active material, a positive electrode binder, a positive electrode conductive agent and a solvent on the positive electrode current collector 212 and drying the slurry. The positive electrode active material is a composite lithium metal oxide, specifically: a lithium nickel cobalt manganese oxide with a layered crystal structure, and the chemical formula is: LiNi x Co y Mn z D j O2, wherein 0.8≤x≤0.9, 0.01≤y≤0.1, 0.01≤z≤0.1, j=1-x–yz, and D is the characteristic element, and the characteristic element D is any one or more of Al, Sr, Ti, Zr, Nb and W.

[0063] The characteristic element D can improve the stability of the positive electrode active material by lattice doping and substitution, surface modification and coating, improving electronic and ionic conductivity, reducing cation mixing and / or inhibiting lattice oxygen loss, etc. The atomic connection between the characteristic element and the lattice of the positive electrode active material can further prevent the byproducts from aggregating and blocking the channel for lithium ion transmission. To further specify, the doping of elements such as Ti, Zr, Nb, and W can improve the lattice stability of positive electrode active materials such as high nickel ternary, reduce the cation mixing phenomenon of transition metal ions such as Ni, Mn, and Co, and reduce the lattice structure changes during the charge and discharge process, thereby improving the cycle stability of the positive electrode active material layer 210; Al doping can promote the formation of BCC phase, thereby improving the corrosion resistance of the material; Al and Nb can improve the electronic conductivity of the positive electrode active material layer 210; Ti and Zr doping can also improve the diffusion kinetics of lithium ions to improve the rate performance and cycle stability of the battery; for lithium-rich manganese-based positive electrode active materials, the redox reaction of oxygen elements is the source of their high capacity, but it is also accompanied by the risk of lattice oxygen loss. The introduction of elements such as Ti and Zr can increase the hybridization degree of transition metals and oxygen atoms TM-O and reduce the precipitation of oxygen. At the same time, the doping of the above elements can also improve the mechanical stability and thermal stability of the positive electrode active material layer 210, and reduce the risk of structural damage and thermal runaway caused by volume expansion and contraction during the charge and discharge process.

[0064] In a specific implementation process, the positive electrode active material layer 210 is formed by coating a slurry prepared by a positive electrode active material, a positive electrode binder, a positive electrode conductive agent and a solvent on the positive electrode current collector 212 and then drying it, wherein the weight ratio of the positive electrode active material, the positive electrode binder and the positive electrode conductive agent is (95%-98%): (1%-2%): (1%-3%). The negative electrode sheet 25 includes a negative electrode active material layer, and the negative electrode active material layer also includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent. The negative electrode active material includes at least two of artificial graphite, natural graphite, silicon oxygen material and silicon carbon material, and corresponds to a first negative electrode active material and a second negative electrode active material; wherein the weight ratio of the first negative electrode active material, the second negative electrode active material, the negative electrode binder and the negative electrode conductive agent is (90%-95%): (1%-4%): (1%-2%): (3%-4%). By optimizing the ratio of the above materials, a balance can be achieved between energy density, conductivity, structural stability and processing performance, thereby achieving the best performance of lithium-ion batteries.

[0065] Further, the electrolyte 3 includes lithium hexafluorophosphate, a solvent and a functional agent for improving the performance of the electrochemical system, the solvent includes one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, and the functional agent includes one or more of vinylene carbonate, methyl formate, ethyl acetate, propyl propionate, and fluoroethylene carbonate. The above lithium hexafluorophosphate provides lithium ions to achieve electrochemical reactions, the solvent is used to provide a good migration environment for charged particles, and the functional agents work together through different mechanisms to significantly improve the performance of lithium ion batteries, wherein both vinylene carbonate and fluoroethylene carbonate can promote the formation of a solid electrolyte interface (SEI) film, improve the first charge and discharge efficiency and cycle stability of the battery, and the SEI film can also inhibit the growth of lithium dendrites and improve the safety of the battery; on the other hand, methyl formate, ethyl acetate, and propyl propionate can reduce the viscosity of the electrolyte 3, increase the transmission rate of lithium ions at low temperatures, and thus improve the low temperature performance of the battery.

[0066] In some optional embodiments, the lithium ion battery has a cycle retention rate of 81-93% after 300 cycles of charge and discharge at a 2C charge rate and a 10C discharge rate. The 300-cycle 2C / 10C cycle capacity retention rate of the constrained lithium ion battery is between 81-93%, which can meet the cycle performance requirements of most existing electrical devices for batteries.

[0067] A second aspect of the present application provides an electrical device, comprising a lithium-ion battery according to any one of the above items.

[0068] The following are specific embodiments:

[0069] Example 1

[0070] Embodiment 1 of the present invention provides a lithium-ion battery, including a housing 1, a winding core 2 and an electrolyte 3, wherein the winding core 2 is formed by winding a positive electrode sheet 21, a separator 23 and a negative electrode sheet 25.

[0071] (1) Prepare a positive electrode sheet 21, including a positive electrode current collector 212 aluminum foil and a positive electrode active material layer 210 coated on both sides of the aluminum foil; wherein, calculated by weight percentage, the positive electrode active material layer 210 includes 95.5% LiNi 0.85 Co 0.05 Mn 0.07 Al 0.03 O2, 0.6% carbon nanotube conductive agent, 2.4% Super-P (conductive carbon black) conductive agent and 1.5% polyvinylidene fluoride PVDF binder; the above substances are added into N-methylpyrrolidone and stirred to form a positive electrode slurry with a solid content of 61%, which is coated on the positive electrode collector 212 to form a positive electrode sheet 21.

[0072] (2) A negative electrode sheet 25 is prepared, including a negative electrode current collector copper foil and a negative electrode active material layer coated on both sides of the copper foil. Calculated by weight percentage, the negative electrode active material layer includes 92% artificial graphite, 4% silicon, 1% conductive agent acetylene black, and 3% negative electrode binder polyacrylic acid. The above substances are added into deionized water and stirred to form a negative electrode slurry with a solid content of 41%, which is then coated on the negative electrode current collector to form a negative electrode sheet 25.

[0073] (3) Prepare electrolyte 3: mix ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1 to obtain an organic solvent, then dissolve fully dried lithium salt LiPF6 in the mixed organic solvent to prepare an electrolyte 3 with a concentration of 1 mol / L, and add 0.1% of functional reagent vinylene carbonate and 0.1% of functional reagent fluoroethylene carbonate.

[0074] (4) The diaphragm 23 includes a high-porosity dynamic diaphragm, a base film PE thickness of 10 um, a ceramic coating thickness of 1 um on both sides, and a PVDF coating thickness of 1 um. The air permeability of the diaphragm 23 is between 80-180 s / 100 mL.

[0075] (5) After the positive electrode sheet 21 and the negative electrode sheet 25 are rolled, slit and die-cut respectively, they are wound together with the separator 23 at the same time. The positive electrode sheet 21, the negative electrode sheet 25 and the separator 23 are wound by a winding machine to form a winding core 2. The positive and negative electrode ears of the winding core 2 are cut and stacked. Then, the positive bus bar and the negative bus bar are welded to the winding core 2 respectively, and then the negative bus bar is welded to the steel shell. An insulating sheet is placed on the top of the positive bus bar, and the positive bus bar is welded to the cap to obtain a lithium-ion battery winding core body, which is loaded into the cylindrical battery shell 1. After completing the injection, sealing and formation processes, the cylindrical lithium-ion battery is obtained.

[0076] Examples 1-3 and Comparative Examples 1-2 are control groups with the content a of the characteristic element as a variable, Examples 2, 4-7 and 10-11 are control groups with the type of the characteristic element as a variable, and Examples 2, 8-9 and Comparative Examples 3-4 are control groups with the porosity p of the diaphragm 23 as a variable. The technical solution of the present application is described below in conjunction with Examples 1-11 and Comparative Examples 1-4.

[0077]

[0078]

[0079] The above Examples 1-11 and Comparative Examples 1-4 were subjected to 300 cycles of cycle retention test and EDS element analysis respectively:

[0080] The test method for 300-cycle cycle retention rate is:

[0081] Take a lithium ion battery prepared according to any of the above embodiments, place it in a 25°C constant temperature box for more than 4 hours, and test it according to the following steps:

[0082] S61: The battery is charged at a constant current of 2C to 4.2V, and charged at a constant voltage to a current of 0.025C, and left to stand for 30 minutes; the battery is discharged at a constant current of 10C to 2.5V, and left to stand for 30 minutes. The first discharge capacity is the initial capacity, which is recorded as C1;

[0083] S62: repeat the above step S61 299 times; the discharge capacity at the 300th cycle is recorded as C300;

[0084] S63: Calculate the 300-cycle retention rate as C300 / C1×100%.

[0085] The qualitative and / or quantitative analysis of the above characteristic elements and F and C elements are all tested by energy dispersive spectrometer (EDS).

[0086] The EDS element analysis method is:

[0087] S71: preparing a cross-section sample of a positive electrode sheet;

[0088] S72: Check the working environment of the EDS detector and calibrate the EDS system;

[0089] S73: Sample loading, collecting the EDS spectrum of the sample to be tested under predetermined electron beam conditions.

[0090] S74: Use EDS analysis software to process and analyze the collected spectra to obtain the types and contents of the elements.

[0091] The specific comparison results of each embodiment are shown in Table 1-Table 3:

[0092] Table 1

[0093]

[0094]

[0095] It can be seen from Table 1 that the element proportion of the characteristic element in the positive electrode active material layer 210 has a great influence on the rate of change of the ratio of the fluorine element to other elements, and when ΔT / (a+p) is greater than 100%, the ΔDCR increase rate used to measure the change in the internal resistance of the battery increases significantly, and the cycle capacity retention rate also decreases accordingly.

[0096] Table 2

[0097]

[0098] It can be seen from Table 2 that the one or more characteristic elements selected in the above embodiments have a good effect of resisting the corrosion of the positive electrode material by the by-products, which is reflected in the high cycle capacity retention rate of the battery.

[0099] Table 3:

[0100]

[0101] It can be seen from Table 3 that when the porosity p is too large, the byproduct growth rate is fast, and when the porosity p is too small, the DC internal resistance growth rate is fast, both of which affect the cycle performance of the battery, and the best porosity p is 30-45%.

[0102] See also Figure 4 In the case of comparative example 1 without characteristic elements, after 300 cycles of 2C / 10C, ​​only 73.2% of the cycle capacity retention rate remained. In example 2, after adding 0.5% additive, under the same cycle conditions, the cycle performance retention rate was greatly improved, and the capacity retention rate reached 92.8%, proving that the addition of characteristic elements to the positive electrode active material proposed in this application can optimize the high-rate cycle performance of lithium-ion batteries.

[0103] In summary, the present application improves the structural stability of the positive electrode active material layer 210 by adjusting the characteristic element content and type of the additives in the positive electrode active material of the lithium-ion battery, thereby ensuring the cycle performance and safety performance of the battery and extending the service life. On the other hand, the porosity of the diaphragm 23 is optimized, thereby reducing the occurrence of side reactions while enhancing the kinetic performance in the electrochemical system, and realizing high-rate charging and discharging of the battery.

[0104] In the description of this specification, reference to the terms "some embodiments", "an example", or similar descriptions means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment are included in at least one embodiment or example. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0105] Although examples of the present embodiment have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present embodiment, and the scope of the present embodiment is defined by the claims and their equivalents.

Claims

1. A lithium-ion battery, comprising a shell, a winding core and an electrolyte, wherein the winding core is formed by winding a positive electrode sheet, a separator and a negative electrode sheet, wherein the porosity p of the separator is 30-45%, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, characterized in that: A characteristic element is added to the positive electrode active material, and the ratio a of the number of atoms of the characteristic element to the total number of atoms of all elements in the positive electrode active material layer is 0.1-0.9%. The lithium ion battery is subjected to a cycle test and the change rate ΔT of the ratio T of the fluorine element and the carbon element content in the cross section of the positive electrode active material layer during the cycle is analyzed. The change rate ΔT further satisfies: 0<ΔT / (a+p)≤100%.

2. The lithium-ion battery according to claim 1, characterized in that The testing method of the porosity p is: S11: Prepare a sample of the diaphragm with a size of 200*100 mm, soak it in dimethyl carbonate three times, and then dry it in a vacuum oven at 60°C for 2 hours. After the sample is cooled, the surface density ρ is obtained by weight-area ratio. 面 ; S12: measuring the average thickness d of the diaphragm sample; as well as S13: Calculate the porosity using the formula, P = {1-[ρ 面 / (0.96*d)]}*100%.

3. The lithium-ion battery according to claim 1, wherein the atomic number ratio a of the characteristic element is tested by: S21: preparing the positive electrode sheet, soaking it in dimethyl carbonate three times, and then drying it in a vacuum oven at 60° C. for 2 hours. After the sample is cooled, preparing a cross-section of the positive electrode sheet using argon ion polishing technology; and S22: using CP-EDS to perform a surface scan on the cross-section corresponding to the positive electrode active material layer, measure all elements in the surface scan area, and obtain the atomic number ratio a of the characteristic elements.

4. The lithium-ion battery according to claim 1, wherein the test method for the change rate ΔT of the ratio T of the fluorine element to the carbon element content during the cycle is: S31: the lithium-ion battery is charged and discharged 300 times under constant current conditions of a 2C charge rate and a 10C discharge rate and an operating voltage of 2.5-4.2V, and the two groups of positive electrode sheets after the first cycle and the 300th cycle are removed, respectively, soaked in dimethyl carbonate three times, and then dried in a vacuum oven at 60° C. for 2 h; S32: After the two groups of positive electrode sheet samples are cooled, cross-section slices of the two groups of positive electrode sheets are prepared by using argon ion polishing technology, and the cross-sections corresponding to the positive electrode active material layers on the cross-section slices of the two groups of positive electrode sheets are locally scanned and characterized by using the CP-EDS method, and the F / C element ratios T1 and T2 in the scanned areas of the two groups of positive electrode sheets are calculated respectively. 300 ;as well as S33: Calculate the change rate ΔT(%) using the formula: ΔT(%)=(T 300 -T1) / (T1)*100%.

5. The lithium ion battery according to claim 1 or 2, characterized in that: The positive electrode active material is a composite lithium metal oxide, specifically: a lithium nickel cobalt manganese oxide (LiNi x Co y Mn z D j O2), wherein 0.8≤x≤0.9, 0.01≤y≤0.1, 0.01≤z≤0.1, j=1-x–yz, D is the characteristic element, and the characteristic element D is any one or more of Al, Sr, Ti, Zr, Nb and W.

6. The lithium-ion battery according to claim 1, characterized in that The lithium-ion battery is measured according to the following steps to measure the DC internal resistance growth rate DCR: S34: at room temperature, the lithium ion battery that has completed one cycle of charge and discharge and the lithium ion battery that has completed 300 cycles of charge and discharge are respectively charged again to their charge cut-off voltage of 4.2V, and then charged at a constant voltage to a current equal to 0.025C, and left to stand for 10 minutes; S35: At room temperature, the lithium-ion battery that has been left to stand is first discharged at a rate of 0.25C for 3 seconds to measure a voltage V1, wherein the discharge current corresponds to I1 amperes, and then discharged at a rate of 2.5C for 3 seconds to measure a voltage V2, wherein the discharge current corresponds to I2 amperes; according to the formula: DCR = (V1-V2) / (I2-I1), the DC internal resistance DCR1 value of the lithium-ion battery that has completed one cycle of charge and discharge and the DCR value of the lithium-ion battery that has completed 300 cycles of charge and discharge are obtained respectively. 300 value; and S36: Further calculate to obtain the DCR growth rate: ΔDCR = (DCR 300 -DCR1) / (DCR1)*100%, and ΔDCR is 27-80%.

7. The lithium-ion battery according to claim 1, characterized in that: The positive electrode active material layer is formed by coating a slurry prepared by the positive electrode active material, the positive electrode binder, the positive electrode conductive agent and the solvent on the positive electrode collector and then drying the slurry, wherein the weight ratio of the positive electrode active material, the positive electrode binder and the positive electrode conductive agent is (95%-98%): (1%-2%): (1%-3%).

8. The lithium-ion battery according to claim 1, characterized in that The negative electrode sheet comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, a negative electrode binder and a negative electrode conductive agent, the negative electrode active material comprises at least two of artificial graphite, natural graphite, silicon oxide material and silicon carbon material, and corresponds to a first negative electrode active material and a second negative electrode active material; wherein the weight ratio of the first negative electrode active material, the second negative electrode active material, the negative electrode binder and the negative electrode conductive agent is (90%-95%): (1%-4%): (1%-2%): (3%-4%).

9. The lithium-ion battery according to claim 1, characterized in that: The electrolyte includes lithium hexafluorophosphate, a solvent and a functional reagent for improving the performance of the electrochemical system, the solvent includes one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, and the functional reagent includes one or more of vinylene carbonate, methyl formate, ethyl acetate, propyl propionate, and fluoroethylene carbonate.

10. The lithium ion battery according to claim 1, characterized in that: The lithium ion battery has a cycle capacity retention rate of 81-93% after 300 cycles of charge and discharge at a 2C charge rate and a 10C discharge rate.

11. An electrical device, characterized in that: Comprising a lithium ion battery according to any one of claims 1 to 10.

Citation Information

Cited By

  • Lithium ion battery

    CN122599508A